Impact of a flexible irrigation reservation system on water savings in a surface irrigation district in northern Italy - Fabiola Gangi; Giorgio Scotti; Claudio Gandolfi; Daniele Masseroni (Journal of Agricultural Engineering)
Improving the efficiency of water use in irrigated areas where surface irrigation is practised is now a goal that must be pursued with persistence, given the effects of climate change on the reduction of surface water availability, especially in Mediterranean areas. The impact of a flexible irrigation booking mechanism on water savings in surface irrigated areas has been investigated in this paper. The water reservation system consisted of an advanced decision support system that linked farmers' requests with the availability of water supply from the irrigation agency. This system was tested as a demonstration project in a portion of a real surface irrigation district located in Northern Italy and the results were compared with those obtained in the second portion of the district where a rigid irrigation calendar was applied. The results showed that, on average over the irrigation season, about 30% of water savings can be achieved if a flexible mechanism of water distribution is adopted, with peaks that can reach up to 60% in wet seasons. Water use efficiency increased significantly from the rigid to the flexible part of the district. These findings demonstrate that transitioning to a more flexible approach to water allocation within surface irrigation districts can yield substantial water savings, thereby enhancing water use efficiency and promoting the sustainability of surface irrigation practices.